CHA2DS2‐VASc score predicts atrial fibrillation recurrence after cardioversion: Systematic review and individual patient pooled meta‐analysis. Issue 3 (11th February 2019) - Vitali, Francesco; Serenelli, Matteo; Airaksinen, Juhani; Pavasini, Rita; Tomaszuk‐Kazberuk, Anna; Mlodawska, Elzbieta; Jaakkola, Samuli; Balla, Cristina; Falsetti, Lorenzo; Tarquinio, Nicola; Ferrari, Roberto; Squeri, Angelo; et al.
Abstract : Background: Despite progresses in the treatment of the thromboembolic risk related to atrial fibrillation (AF), the management of recurrences remains a challenge. Hypothesis: To assess if congestive heart failure or left ventricular systolic dysfunction (CHA2 DS2 ‐VASc) score is predictive of early arrhythmia recurrence after AF cardioversion. Methods: Systematic review and individual patient pooled meta‐analysis following Preferred Reporting Items for Systematic reviews and Meta‐Analyses guidelines. Inclusion criteria: observational trials in patients with AF undergoing cardioversion, available data on recurrence of AF and available data on CHA2 DS2 ‐VASc score. Clinical studies of interest were retrieved by PubMed, Cochrane Library, and Biomed Central. Seven authors were contacted for joining the patient level meta‐analysis, and three shared data regarding anthropometric measurements, risk factors, major comorbidities, and CHA2 DS2 ‐VASc score. The primary outcome was the recurrence of AF after cardioversion in patients free from antiarrhythmic prophylaxis. Univariate and multivariate logistic regression was performed. Results: Overall, we collect data of 2889 patients: 61% were male, 50% with hypertension, 12% with diabetes, and 23% with history of ischemic heart disease. The median CHA2DS2‐VASc score was 2.. At the multivariate analysis, chronic kidney disease (odds ratio [OR] 1.94; 95% confidence interval [CI] 1.12‐3.27; P = 0.01), peripheral artery disease (OR 1.65; 95% CI 1.23‐2.19; P < 0, 0001), previous use of beta blockers (OR 1.5; 95% CI 1.19‐1.88; P < 0.0001), and CHA2DS2‐VASc score > 2 (OR 1.37; 95% CI 1.1‐1.68; P  = 0.002) were independent predictors of early recurrence of AF. Conclusions: CHA2DS2‐VASc score predicts early recurrence of AF in the first 30 days after electrical or pharmacological cardioversion. Protocol registration PROSPERO (CRD42017075107).